A "Era do ônibus": formação, ascensão e hegemonia do empresariado de ônibus urbano de Belo Horizonte 1950-1990 - André Henrique de Brito Veloso (2023)
The research presented in this thesis seeks to identify the origins and the formation process of the urban bus business in the city of Belo Horizonte between the decades of 1950 and 1980. We begin from the construction of conceptual elements that allow us to understand the development of the so-called ”Urban Mobility Systems" in the context of the intense urbanization process experienced in Brazil throughout the 20th century. In this sense, we seek to reconstitute the development of tram lines and their service capacity in Belo Horizonte during the first half of the century to understand the roots and fractures that allowed for the growth of roadway systems and the hegemony of the bus as a mean of transportation in urban spaces during the following decades. A vast set of primary and secondary sources is mobilized in order to reproduce the development of bus lines and their service capacity between 1952 and 1979, which allows us to understand the rapid growth of a diverse set of bus entrepreneurs throughout this period. The low capacity of government action added to intense demographic growth, in a context where the system was completely financed by ticketing, creates a false perception of a free market and meritocracy. However, the research finds that the high number of companies and low quality of service provided in the city contributed to the widespread perception of a crisis of the service by the late 1970s, which, in turn, led to a serious attempt to reorganize public transportation in Minas Gerais, with the advent of METROBEL. The first two years of operation of this state-owned company, a late result of the state's technocratic tradition, were enough to permanently alter the business organization in the sector and its capacity to operate. The process of modernization made by external forces contributed to the expansion of this business in both the state's and national territories, especially for cities in the North and Northeast regions; the state also acted as a protagonist with the - also delayed - creation of structures of federal representation for the category and its political performance within the national transportation sector. Finally, the presence of this group of business-owners in crucial debates concerning the federal regulation of the transportation system by the late 1980s, as in the case of determining bus-passes as mandatory employee benefits, is seen through the prism of the current and terminal crisis of fare financing of national public transportation. The specific historical context surrounding the formation of the most significant generation of bus entrepreneurs in Brazil is thus understood as a central element that allow for the current debates on the regulatory framework of public transportation to be reconsidered. And so that a perspective of public and popular control of transportation, with the restructuring of the role of the service operator, can prevail.